An Abdominal Mass: A Case of Jekyll and Hyde? - Gendeh BS,; Kosai NR,; Belani LK,; Taher MM,; Reynu R,; Ramzisham AR, (Penerbit UKM, 2015)
Right iliac fossa pain can often be misdiagnosed as something sinister or benevolent despite assistance with state of the art imaging techniques. This is particularly more challenging in the female gender whereby the error of managing a right iliac fossa pain may approach forty percent. A 66-year-old lady, ten years post-menopause, presented with a week history of progressively worsening right iliac fossa pain. Malignancy was suspected with a palpable abdominal mass. Computed tomography was suggestive of an abscess collection, but a needle aspirate produced brown faecal material suggestive of a diverticulitis. An exploratory appendisectomy revealed a non malignant appendicular abscess. In conclusion, when clinical and imaging assessments are inconclusive, an exploratory laparotomy for a surgical excision is warranted primarily if malignancy is suspected.